Production of cytokines, vascular endothelial growth factor, matrix metalloproteinases, and tissue inhibitor of metalloproteinases 1 by tenosynovium demonstrates its potential for tendon destruction in rheumatoid arthritis. - Jain, A; Nanchahal, J; Troeberg, L; Green, P; Brennan, F (2001)
OBJECTIVE: To investigate the role of proinflammatory cytokines, vascular endothelial growth factor (VEGF), matrix metalloproteinases (MMPs), and tissue inhibitor of metalloproteinases 1 (TIMP-1) in the destruction of tendons by tenosynovium in rheumatoid arthritis (RA). METHODS: Synovial specimens were obtained from encapsulating tenosynovium (n = 17), invasive tenosynovium (n = 13), and wrist joints (n = 17) in 18 RA patients undergoing wrist extensor tenosynovectomy. Synovial membrane cells were dissociated from connective tissue by enzyme digestion and cultured in vitro for 48 hours, and harvested supernatants were assayed for the cytokines tumor necrosis factor alpha (TNFalpha) and interleukin-6 (IL-6), VEGF, MMPs 1, 2, 3, and 13, and TIMP-1 by enzyme-linked immunosorbent assay. Gelatin zymography was performed to demonstrate enzyme activity. Statistical analysis was performed using Student's paired 2-tailed t-tests for parametric data and the Wilcoxon signed rank test for nonparametric data. RESULTS: MMP-1 and MMP-13 levels were approximately 2.5-fold higher in invasive tenosynovium compared with encapsulating tenosynovium. Levels of MMP-2 were approximately 1.5-fold higher in invasive tenosynovium compared with both encapsulating tenosynovium and wrist joint synovium. MMP-13 (P = 0.009) and IL-6 (P = 0.03) levels were significantly lower in encapsulating tenosynovium compared with wrist joint synovium. Levels of VEGF, TIMP-1, TNFalpha, and MMP-3 were similar in all synovial sample groups. Zymography demonstrated enzyme activity in all synovium samples from all 9 patients assessed. CONCLUSION: Tenosynovium produces proinflammatory cytokines and proteolytic enzymes that are important in the tissue degradation seen in RA. Increased production of the enzymes MMP-1, MMP-2, and MMP-13 by invasive tenosynovium suggests a possible explanation for the worse prognosis and increased rupture rate associated with invasive tenosynovitis in RA. Production of VEGF by tenosynovium suggests that angiogenesis may have a role in tenosynovial proliferation and invasion of tendons.